Power losses evaluation in low voltage distribution network: a case study of 250 kVA, 11/0.416 kV substation - Emad Hussen Sadiq; Rakan Khalil Antar; Safer Taib Ahmed (Indonesian Journal of Electrical Engineering and Computer Science, 2022)
Nowadays, the electrical system is more complicated duet to the continuous growing. Power losses is the biggest challenges for distribution network operators. There are several causes for technical losses. Losses caused by unbalanced phase current are one of the main reasons which can be minimized by small investment through dedicating a technical line staff. As a result of connecting many single loads to three phase four wire power supplies, the current flowing in each phase will be unequal and accordingly there will be a current flowing in the neutral wire. Unbalancing currents in phases can lead to increase the conductor temperature and accordingly the conductor resistance is higher which contribute to increase the power losses. Loss reduction can lead to enormous utility saving. Besides, it increases system capacity and save more money which can be used later for future planted system. This study concentrated on the amount of copper losses in distribution networks as a result of unequal loading of the three phases four wires network. The distribution network is more efficient and more economic assuming that the right procedure is applied to balance the distribution system and achieve the required calculations which require a little investment.